2004
DOI: 10.1194/jlr.m300468-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of the murine mucin gene 1 decreases susceptibility to cholesterol gallstone formation

Abstract: Gallbladder mucins play a critical role in the pathogenesis of cholesterol gallstones because of their ability to bind biliary lipids and accelerate cholesterol crystallization. Mucin secretion and accumulation in the gallbladder is determined by multiple mucin genes. To study whether mucin gene 1 ( Muc1 ) influences susceptibility to cholesterol cholelithiasis, we investigated male Muc1 -deficient ( Muc1 ؊ / ؊ ) and wild-type mice fed a lithogenic diet containing 1% cholesterol and 0.5% cholic acid for 56 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 38 publications
3
23
0
1
Order By: Relevance
“…Until now, besides several long-term investigations, the only gallbladder proteins/genes that have been implicated in downstream defects related to cholesterol gallstone development have been mucin genes (13). It has also been shown that mucin is upregulated by hydrophobic BAs, and its expression level in the gallbladder affects susceptibility to cholesterol gallstone formation in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, besides several long-term investigations, the only gallbladder proteins/genes that have been implicated in downstream defects related to cholesterol gallstone development have been mucin genes (13). It has also been shown that mucin is upregulated by hydrophobic BAs, and its expression level in the gallbladder affects susceptibility to cholesterol gallstone formation in mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the gallbladder acts to concentrate bile through mechanisms that involve the adsorption of water and electrolytes (5,6), which are largely dependent upon Na ϩ /H ϩ exchange at the apical membrane of the gallbladder epithelium (GBE) (7)(8)(9). Gallstone formation is also related to an increase in gallbladder secretion of mucin, which correlates with the promotion of crystallization in experimental and human gallstone disease (10)(11)(12)(13). Relevant to the production of cholesterol crystals is the rapid aggregation of cholesterol-phospholipid vesicles that occurs in the gallbladder lumen.…”
mentioning
confidence: 99%
“…Primer Express Software (Applied Biosystems, Foster City, CA) was used to design the primers ( Table 1) based on sequence data available from GenBank. Real-time PCR assays for all samples were performed in triplicate (22). Relative mRNA levels were calculated using the threshold cycle of an unknown sample against a standard curve with known copy numbers.…”
Section: Quantitative Real-time Pcr Assaymentioning
confidence: 99%
“…Furthermore, some biliary factors such as secretion rates of biliary lipids (bile salts, cholesterol, and phospholipid) and cholesterol content of bile, as well as sizes, molecular compositions, and hydrophilic-hydrophobic indexes of biliary bile salt pool, could together exert a major influence on the efficiency of intestinal cholesterol absorption (48). However, our previous studies (51) showed that targeted disruption of the Muc1 gene does not influence either biliary lipid secretion or biliary bile salt species and pool sizes in chow-fed mice. Taken together, our results reveal that these lumenal and biliary factors are not a major contributor to the reduction of cholesterol absorption in Muc1 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%